Blastomyces helicus, a New Dimorphic Fungus Causing Fatal Pulmonary and Systemic Disease in Humans and Animals in Western Canada and the United States. (7th June 2018) - Schwartz, Ilan S; Wiederhold, Nathan P; Hanson, Kimberly E; Patterson, Thomas F; Sigler, Lynne
Abstract : Blastomyces helicus is an emerging dimorphic fungus that causes fatal pulmonary and systemic disease predominantly in immunocompromised humans and companion animals in western and central regions of Canada and the United States. Abstract: Background: Blastomyces helicus (formerly Emmonsia helica ) is a dimorphic fungus first isolated from a man with fungal encephalitis in Alberta, Canada. The geographic range, epidemiology, and clinical features of disease are unknown. Methods: We reviewed human and veterinary isolates of B. helicus identified among Blastomyces and Emmonsia isolates at the University of Alberta Microfungus Collection and Herbarium, University of Texas Health San Antonio's Fungus Testing Laboratory, and Associated Regional and University Pathologists Laboratories. Isolates were selected based on low Blastomyces dermatitidis DNA probe values and/or atypical morphology. Species identification was confirmed for most isolates by DNA sequence analysis of the internal transcribed spacer with or without D1/D2 ribosomal RNA regions. Epidemiological and clinical data were analyzed. Results: We identified isolates from 10 human and 5 veterinary cases of B. helicus infection; all were referred from western regions of Canada and the United States. Isolates remained sterile in culture, producing neither conidia nor sexual spores in the mycelial phase, but often producing coiled hyphae. Isolates were most frequently cultured from blood and bronchoalveolar lavage in humans and lungs in animals. Most infected persons were immunocompromised. Histopathological findings included pleomorphic, small or variably sized yeast-like cells, with single or multiple budding, sometimes proliferating to form short, branching, hyphal-like elements. Disease carried a high case-fatality rate. Conclusions: Blastomyces helicus causes fatal pulmonary and systemic disease in humans and companion animals. It differs from B. dermatitidis in morphological presentation in culture and in histopathology, by primarily affecting immunocompromised persons, and in a geographic range that includes western regions of North America.